An Integrated Morphological Framework for Analyzing Informal Settlements: The Case of Saadi Neighborhood, Shiraz - Nezhadmasoum, Sanaz; Vehbi, Beser Oktay (Mdpi, 2025)
Informal settlements accommodate more than one billion people worldwide, yet their intricate urban forms are frequently perceived as chaotic, which impedes the formulation of sustainable upgrading strategies. The main objective of this research is to bridge a major methodological gap by developing analytical tools that can systematically decode the inherent spatial logic of such environments. This paper develops and applies an integrated four-part morphological framework designed to provide a deep, form-based reading of informal urbanism. The framework's indicators were systematically derived from an extensive review of the literature and subsequently validated through the Fuzzy Delphi Method (FDM) with a panel of 15 experts, ensuring analytical robustness. The validated framework was then applied to the Saadi neighborhood, a representative informal settlement in Shiraz, Iran, using a multi-scalar, mixed-methods approach that integrated GIS, remote sensing, and in-depth field surveys. The analysis produced a comprehensive analytical atlas, culminating in a detailed morphological profile. The findings identify Saadi's urban form not as disordered, but as a 'consolidating, low-rise, fine-grained fabric shaped by topography,' revealing a clear, self-organized spatial logic. The study concludes that the proposed framework is a robust and replicable tool for moving beyond pejorative descriptions of informality. By providing an evidence-based method to read the physical language of these settlements, the approach offers a crucial foundation for developing more context-sensitive and sustainable urban upgrading strategies.
Keywords: urban morphology; informal settlements; analytical framework; sustainable urbanism; Fuzzy Delphi Method; Shiraz; form-based analysis